THE EFFECTIVENESS OF LAW ENFORCEMENT AGAINST PERPETRATORS OF DESTRUCTION OF TOURISM OBJECTS IN NORTH TORAJA - Salamba , Yogistry Pakita (ANAYASA : Journal of Legal Studies, 2024)
The research aims to analyze the enforcement of sanctions against perpetrators of vandalism at tourist attractions in North Toraja and the obstacles to implementing sanctions in law enforcement against perpetrators of vandalism at tourist attractions based on Regional Regulation Number 7 of 2016. The research employed an empirical research method, using statutory and conceptual approaches. This research used primary and secondary data. Primary data was obtained through field research using interviews and observations, while secondary data was obtained through a literature study. The data obtained was then analyzed qualitatively and described to answer the research problem. The research results show that the sanction enforcement of Regional Regulation Number 7 of 2016 concerning the Implementation of Tourism in North Toraja has not complied with these regulations. In particular, cases of destruction of Ke'te' Kesu' carried out by perpetrators that are imposed with customary punishment, it is marked by the large number of unresolved cases and weak enforcement of sanctions. Obstacles in implementing sanctions in law enforcement are caused primarily by delays in information to the Civil Service Police Unit resulting in initial administrative action before being handed over to the Prosecutor's Office. Another obstacle is the absence of a memorandum of understanding between the Police, Prosecutor's Office, and Court, as well as budget limitations which affect the capacity of the Civil Service Police Unit (Satpol PP) to protect tourists. A comprehensive approach is needed, including law enforcer training, inter-agency coordination, public legal education, and review of Regional Regulations to improve the fairness and appropriateness of sanctions.